Runs of homozygosity reveal genome‐wide autozygosity in Italian sheep breeds. (15th January 2018) - Mastrangelo, S.; Ciani, E.; Sardina, M. T.; Sottile, G.; Pilla, F.; Portolano, B.; ,
Summary: The availability of dense single nucleotide polymorphism (SNP) assays allows for the determination of autozygous segments based on runs of consecutive homozygous genotypes (ROH). The aim of the present study was to investigate the occurrence and distribution of ROH in 21 Italian sheep breeds using medium‐density SNP genotypes in order to characterize autozygosity and identify genomic regions that frequently appeared in ROH within individuals, namely ROH islands. After filtering, the final number of animals and SNPs retained for analyses were 502 and 46 277 respectively. A total of 12 302 ROH were identified. The mean number of ROH per breed ranged from 10.58 (Comisana) to 44.54 (Valle del Belice). The average length of ROH across breeds was 4.55 Mb and ranged from 3.85 Mb (Biellese) to 5.51 Mb (Leccese). Valle del Belice showed the highest value of inbreeding on the basis of ROH ( F ROH  = 0.099), whereas Comisana showed the lowest ( F ROH  = 0.016), and high standard deviation values revealed high variability in autozygosity levels within each breed. Differences also existed in the length of ROH. Analysis of the distribution of ROH according to their size showed that, for all breeds, the majority of the detected ROH were <10 Mb in length, with a few long ROH >25 Mb. The levels of ROH that we estimated here reflect the inbreeding history of the investigated sheep breeds. These results also highlight that ancient and recent inbreeding have had an impact on the genome of the Italian sheep breeds and suggest that several animals have experienced recent autozygosity events. Comisana and Bergamasca appeared as the less consanguineous breeds, whereas Barbaresca, Leccese and Valle del Belice showed ROH patterns typically produced by recent inbreeding. Moreover, within the genomic regions most commonly associated with ROH, several candidate genes were detected.